Economic evaluation of the environmental impact of shipping from the perspective of CO2 emissions - Elyakim Ben-Hakoun; Mordechai Shechter; Yehuda Hayuth (Journal of Shipping and Trade (JST), 2016)
In this research we evaluate the environmental economic impact of shipping from the perspective of CO2 emissions by implementing Marine Emission Trading Scheme (METS), as defined. This trading scheme is based on the EU Emissions Trading System (EU-ETS) program with adjustments for the shipping industry's needs. First, we evaluate the socio-economic cost of carbon emissions from seaborne trade activity per borne ton and per consumed ton fuel in both Business as Usual (BAU) and METS state. Then we continue to evaluate the relative socio-economic effect with regional segmentation, transportation mode, and the expected effect on the shipping industry from both the economic and environmental perspective. The METS economic model is calibrated with the Fuel Consumption data (FC), forecasted FC growth rate (based on the proportion between FC growth rate and global trade growth rate), forecasted emission abatement rate (based on EU-ETS actual performance) and Emission Unit Allowance (EUA) prices. This generates an economic evaluation based on multiple CO2 emission scenarios, allowing us to estimate the socio-economic impact on the environment from seaborne trade activity per borne ton criteria and per consumed ton fuel criteria in BAU State and METS State.The research shows that METS is effective, for an annual reduction rate of 7 % or more, but its efficiency is dependent upon the low growth rate of fuel demand.International shipping, in a state of BAU, is expected to increase its economic environmental influence by 356 % from 2007 to 2030, with the maximum increase of CO2 emissions estimated at 324 %. In contrast, implementation of METS is expected to decrease CO2 emissions between 54 and 93 % with the maximum emission growth rate at 207 %, and the minimum emission growth rate at 110 %. In relation to the BAU state and the external costs per ton of fuel consumed under BAU is expected to grow by 16 %, although with the expected rise in fuel prices this rate could decrease to 5 %.We found that under METS regulation this rate would grow only by up to 10 % and decrease up to 4 %. In addition, we found that calculations of external cost per transported ton are likely to create an imbalance between payments and actual contribution to the pollution problem.To conclude, the current sea freight tariff system does not account for the external costs of CO2 emissions, and therefore we suggest that International Maritime Organization (IMO), must take charge, lead and coordinate an international program of emission trade, that could achieve effective reductions with minimum impact on business activity.
Keywords: 650; Carbon Emission; International Maritime Organization; Marginal Abatement Cost; Shipping Industry; Emission Permit